Investigation on the intermolecular interactions in aliphatic isocyanurate liquids: revealing the importance of dispersion - Lenzi, Veniero (2019)
Aliphatic isocyanurates are nowadays used routinely in the development of advanced materials like polyurethane nanocomposites and 3D-printed components, due to their versatile reactivity and the good mechanical and optical properties they confer to the final material. In these applications, a control of the properties at the micro- and nanoscale is desired, therefore a deep understanding of intermolecular interactions is required. Using ab-initio calculations and molecular dynamics simulations, the intermolecular interactions of aliphatic isocyanurates are investigated in detail. The presence of an isocyanate-isocyanurate interaction is demonstrated, and the strong dispersion character of isocyanurate-based interactions is revealed. Calculations of the free energy of binding of the different interactions in gas and liquid phase are provided. The microscopic structure of aliphatic functional and non-functional isocyanurates is analysed and related to the different interaction types, and finally their possible relationship with macroscopic dynamic variables is discussed